Prevalence and Risk Factors of Metabolic Syndrome Among Patients With Hypertension (International Journal of Scientific Research and Management (IJSRM), 2024)
Background: Metabolic syndrome (MetS) is a serious public health and clinical concern since its prevalence has been rising over the past few decades and is now approaching epidemic levels. Objective: To estimate the prevalence and risk factors of MetS in Jordanian adults with confirmed diagnoses of hypertension. Method: This is a hospital-based cross-sectional study conducted among Jordanian patients with hypertension who were followed at outpatient clinics at King Hussien Medical Center. Metabolic syndrome was diagnosed based on International Diabetes Federation (IDF) criteria. Data on socio-demographic, clinical, and anthropometric characteristics were collected from 336 hypertensive patients from June to October 2023. Descriptive analysis was utilized to assess the prevalence of MetS, and binary logistic regression analysis was used to determine independent risk factors for MetS. Result: The overall prevalence of MetS was 33.6% (33.6% in males and 66.4% in females). Advanced age (OR = 2.006, 95% CI: 1.280 - 2.913), increased waist circumference (OR = 2.864, 95% CI: 1.534 - 4.322), increased systolic blood pressure (OR = 1.073, 95% CI: 1.041 - 1.105), overweight (OR = 5.522, 95% CI: 1.371 - 7.422), and obesity (OR = 7.521, 95% CI: 4.520 - 9.016) were associated factors that increased the risk of Mets (P<0.05). Meanwhile, high physical activity (OR = 0.321, 95% CI: 0.107–0.961) decreased the risk of MetS (P<0.05). Conclusion: One-third of the hypertensive patients had MetS, thus highlighting the necessity of early screening and vigorous treatment of all hypertensive individuals to reduce the occurrence of cardiovascular events.